3.7(new) solved by 김선호 정양헌 김준현

2070 days ago by math2013

A=matrix(3,6,[1,3,-2,1,0,0,1,4,-2,0,1,0,3,0,2,0,0,1]) B=matrix(3,6,[1,1,0,1,0,0,0,1,1,0,1,0,1,0,1,0,0,1]) print "A=" print A print "rref of A" print A.rref() print "B=" print B print "rref of B" print B.rref() 
       
A=
[ 1  3 -2  1  0  0]
[ 1  4 -2  0  1  0]
[ 3  0  2  0  0  1]
rref of A
[   1    0    0    1 -3/4  1/4]
[   0    1    0   -1    1    0]
[   0    0    1 -3/2  9/8  1/8]
B=
[1 1 0 1 0 0]
[0 1 1 0 1 0]
[1 0 1 0 0 1]
rref of B
[   1    0    0  1/2 -1/2  1/2]
[   0    1    0  1/2  1/2 -1/2]
[   0    0    1 -1/2  1/2  1/2]
A=
[ 1  3 -2  1  0  0]
[ 1  4 -2  0  1  0]
[ 3  0  2  0  0  1]
rref of A
[   1    0    0    1 -3/4  1/4]
[   0    1    0   -1    1    0]
[   0    0    1 -3/2  9/8  1/8]
B=
[1 1 0 1 0 0]
[0 1 1 0 1 0]
[1 0 1 0 0 1]
rref of B
[   1    0    0  1/2 -1/2  1/2]
[   0    1    0  1/2  1/2 -1/2]
[   0    0    1 -1/2  1/2  1/2]